Photoproducts of carminic acid formed by a composite from Manihot dulcis waste - Antonio Cisneros, Cynthia Magaly; Dávila-Jiménez, Martín M.; Elizalde-González, María P.; García-Díaz, Esmeralda (Food Chemistry, 2015)
Carbon–TiO2 composites were obtained from carbonised Manihot dulcis waste and TiO2 using glycerol as an additive and thermally treating the composites at 800 °C. Furthermore, carbon was obtained from manihot to study the adsorption, desorption and photocatalysis of carminic acid on these materials. Carminic acid, a natural dye extracted from cochineal insects, is a pollutant produced by the food industry and handicrafts. Its photocatalysis was observed under different atmospheres, and kinetic curves were measured by both UV–Vis and HPLC for comparison, yielding interesting differences. The composite was capable of decomposing approximately 50% of the carminic acid under various conditions. The reaction was monitored by UV–Vis spectroscopy and LC-ESI-(Qq)-TOF-MS-DAD, enabling the identification of some intermediate species. The deleterious compound anthracene-9,10-dione was detected both in N2 and air atmospheres.